The significance of a new parameter – plasma protein binding – in therapeutic drug monitoring and its application to carbamazepine in epileptic patients. Issue 45 (26th May 2017) - Gao, Jing-lin; Wang, Xin-yu; An, Jing; Du, Chao-hui; Li, Meng-jiao; Ma, Hai-yan; Zhang, Li-na; Bian, Jing; Jiang, Ye
Abstract : The primary cause of the variability of C f in pharmacology is the change in plasma protein binding (PPB), thus PPB monitoring should be applied to a better individualization of drug dosage regimens in clinical patients. Abstract : Free drug concentration ( C f ) is instantaneous and susceptible to sampling time, which can confuse clinicians and cause them to adjust the dosage regimen. In the present work, we indicated a new parameter, the plasma protein binding (PPB) of clinical plasma samples, and discussed its application in TDM (Therapeutic Drug Monitoring). Furthermore, carbamazepine was selected as a model drug to develop a simple pretreatment method for the determination of PPB, in which C f and C t can be simultaneously analyzed in one plasma sample using a single device. Our results demonstrated that this proposed method exhibited some advantages, including perfect recovery (approximately 100%) and high precision (CV% < 3.0%). Furthermore, it achieved successful application in real plasma samples. Individual differences in PPB (from 10.1–68.9%) were among patients, and in additon, between the patients and healthy people ( p < 0.05). Moreover, there was a weak correlation between C t and C f ( r 2 = 0.470 and p < 0.05), so the C f of CBZ cannot be estimated from C t . However, the primary cause of the variability of C f is the change in PPB. As a consequence, applying PPB to guide individual dose adjustment is more accurate and more scientific than using C f or C t .